Experiences of older beneficiaries of private medical aid schemes and retirement annuities for the development of healthy ageing models - Benzimra, Alison (Research of GSB, 2018)
This study explores the experiences and perceptions of older beneficiaries of private medical aid schemes and retirement annuities. Its main research question is: What motivates, challenges and concerns older research participants when it comes to maintaining their good health and financial well-being? Its research objective is to place these lived experiences within the context of the private health and finance sectors of South Africa in order to develop healthy ageing models. It arises out of the increase in longevity and the potential increase of healthcare expenses in old age. The key concepts in this study are ageing frameworks and whealthcare: the relationship between the financial services industry and healthcare sector. A qualitative approach is used with semi-structured interviews with professionals in the healthcare and finance sectors and individuals in the retirement phase of their lives. The study is significant as it gives a deeper understanding of the realities of older people who access private sector services and it provides a framework for greater synergy between the finance and health sectors to promote healthy ageing and prepare individuals for the financial implications of healthcare costs in later age.